2003
DOI: 10.1175/1520-0442(2003)016<4079:dmutsc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Do Models Underestimate the Solar Contribution to Recent Climate Change?

Abstract: Current attribution analyses that seek to determine the relative contributions of different forcing agents to observed near-surface temperature changes underestimate the importance of weak signals, such as that due to changes in solar irradiance. Here a new attribution method is applied that does not have a systematic bias against weak signals.It is found that current climate models underestimate the observed climate response to solar forcing over the twentieth century as a whole, indicating that the climate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 46 publications
7
77
1
2
Order By: Relevance
“…The sensitivity to SST also highlights the need for the reliable reconstruction of the historical evolution, especially before 1950. The early 20th-century Arctic warming may be partly due to the increased GHGs, reduced volcanic aerosols, and solar irradiance changes (11,12,(49)(50)(51)(52)(53). However, it remains challenging to quantify their contribution due to limited observations and uncertainties of model response (54).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The sensitivity to SST also highlights the need for the reliable reconstruction of the historical evolution, especially before 1950. The early 20th-century Arctic warming may be partly due to the increased GHGs, reduced volcanic aerosols, and solar irradiance changes (11,12,(49)(50)(51)(52)(53). However, it remains challenging to quantify their contribution due to limited observations and uncertainties of model response (54).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Detection-attribution studies using climate models have found a feedback amplification of the input centennial TSI variation by a factor of β S ≈ 3 (e.g. Stott et al 2003;Ingram 2006), which would reduce the required TSI change to near 10 W m −2 . However, one should note that some of this amplification may be unreal and due to a metrology factor (discussed in §9), which has been reported as exaggerating the downward drift in GMAST in the middle of the twentieth century.…”
Section: Some Basic Considerationsmentioning
confidence: 99%
“…Recent climate models suggest that reconstructions of Earth's climate would be more compatible with smaller irradiance variations (Feulner 2011;Schmidt et al 2012), but earlier work did indicate that solar influences may have been underestimated (Stott et al 2003). In this Note we examine the TSI reconstructions of S2011 the light of relevant solar and stellar data.…”
Section: Introductionmentioning
confidence: 98%